Comparative effects of moderate and high-intensity training on immune activation in myocarditis: a review of preclinical and clinical evidence - Ferraro, Bartolo; Buela Alvarado, Cristina Alejandra; Mink, Jonas; Weckbach, Ludwig T. (Frontiers in Pharmacology, 2025)
Exercise intensity plays a critical role in influencing immune responses during myocarditis, a condition characterized by inflammation of the cardiac tissue. Based on preclinical and clinical evidence, this review examines how moderate versus high-intensity training affects immune activation in myocarditis. Studies involving animals suggest that moderate exercise may reduce inflammation and support immune regulation, while high-intensity training often exacerbates pro-inflammatory responses and worsens cardiac injury. Limited clinical data support these findings, indicating that moderate exercise could be safe or even beneficial in stable cases, whereas high-intensity exercise poses risks, particularly during active disease. Understanding these contrasting effects is essential for developing exercise recommendations for patients with myocarditis, balancing the need for recovery with immune safety. Further research is necessary to identify optimal exercise strategies for this vulnerable population.